Nanovesicles From Lactobacillus johnsonii N6.2 Reduce Apoptosis in Human Beta Cells by Promoting AHR Translocation and IL10 Secretion - Teixeira, Leandro D.; Harrison, Natalie A.; da Silva, Danilo R.; Mathews, Clayton E.; Gonzalez, Claudio F.; Lorca, Graciela L. (Frontiers in Immunology, 2022)
L. johnsonii N6.2 releases nano-sized vesicles (NVs) with distinct protein and lipid contents. We hypothesized that these NVs play a central role in the delivery of bioactive molecules that may act as mechanistic effectors in immune modulation. In this report, we observed that addition of NVs to the human pancreatic cell line βlox5 reduced cytokine-induced apoptosis. Through RNAseq analyses, increased expression of CYP1A1, CYP1B1, AHRR, and TIPARP genes in the AHR pathways were found to be significantly induced in presence of NVs. AHR nuclear translocation was confirmed by confocal microscopy. The role of NVs on beta cell function was further evaluated using primary human pancreatic islets. It was found that NVs significantly increased insulin secretion in presence of high glucose concentrations. These increases positively correlated with increased GLUT6 and SREBF1 mRNA and coincided with reduced oxidative stress markers. Furthermore, incubation of NVs with THP-1 macrophages promoted the M2 tolerogenic phenotype through STAT3 activation, expression of AHR-dependent genes and secretion of IL10. Altogether, our findings indicate that bacterial NVs have the potential to modulate glucose homeostasis in the host by directly affecting insulin secretion by islets and through the induction of a tolerogenic immune phenotype.